TRANSFORMASI LIMBAH TEMPE MENJADI PUPUK ORGANIK CAIR RAMAH LINGKUNGAN - Eva Shopia Suwandi; Rizky Maulana; Sandi Setiadi (PT. ABIG RIZKY PUBLISHER, 2025)
Tempe is a fermented soybean product commonly consumed by Indonesian people. The existence of the tempe industry is quite easy to find, especially in Gunungbatu Village, Cilograng District, Lebak Regency, Banten Province. In addition to contributing to the community's economy, this industry also raises a number of problems. The tempe production process produces liquid waste that has the potential to pollute the environment if not handled properly. One solution to reduce the negative impact of this waste is to process it into liquid organic fertilizer. This program aims to enable the community to utilize liquid tempe waste as a basic ingredient for liquid organic fertilizer, so that waste is not wasted and can provide benefits. Before the program was implemented, observations were made on the number of tempe industries that would be used as samples. Waste sampling was carried out from five different tempe production locations. In implementing the program, a socialization method was used through counseling and direct practice. The fertilizer making process is carried out by utilizing tempe waste and EM4 as an activating material. This program consists of two main parts: socialization containing information about environmental issues, waste, and the benefits of liquid organic fertilizer; and fertilizer making practices that are carried out directly and followed by industry players. The entire series of activities went well and are expected to be a sustainable step in utilizing tempe waste to reduce environmental pollution.